Cooking with the LORAX - Fry, Sonali; Conley, Anthony (New York : Random House, 2022)
In simple rhyming text, the Lorax is hungry and decides to make himself a salad using fruit and vegetables he picks from his garden.
Primary.
Keywords: Readers (Primary); Fruit -- Juvenile fiction; Vegetables -- Juvenile fiction; Gardens -- Juvenile fiction; Readers (Publications).; Stories in rhyme